2015
DOI: 10.1002/anie.201504156
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fluorophores that Target Small Molecules to the Endoplasmic Reticulum of Living Mammalian Cells

Abstract: The endoplasmic reticulum (ER) plays critical roles in the processing of secreted and transmembrane proteins. To deliver small molecules to this organelle, we synthesized fluorinated hydrophobic analogues of the fluorophore rhodol. These cell-permeable fluorophores are exceptionally bright, with quantum yields of ~ 0.8, and specifically accumulate in the ER of living HeLa cells, as imaged by confocal laser scanning microscopy. To target a biological pathway controlled by the ER, we linked a fluorinated hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…These compounds were designed based on structural similarity to fluorinated hydrophobic rhodol fluorophores 12 that are known to accumulate in the ER of mammalian cells, Two resorufamines bearing hexyl (HRA) and 2-methoxyethyl ( 10 ) substituents could be readily prepared in only two steps from the commercially available fluorophore resorufin, making them highly cost-effective molecular probes. The fluorescence emission of these compounds is red-shifted compared to resorufin, making them spectrally orthogonal to many blue and green fluorophores, but they retain high quantum yields.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds were designed based on structural similarity to fluorinated hydrophobic rhodol fluorophores 12 that are known to accumulate in the ER of mammalian cells, Two resorufamines bearing hexyl (HRA) and 2-methoxyethyl ( 10 ) substituents could be readily prepared in only two steps from the commercially available fluorophore resorufin, making them highly cost-effective molecular probes. The fluorescence emission of these compounds is red-shifted compared to resorufin, making them spectrally orthogonal to many blue and green fluorophores, but they retain high quantum yields.…”
Section: Discussionmentioning
confidence: 99%
“…532 nm). 12 Some of these compounds are thought 9, 13, 14 to selectively accumulate in the ER because of the unique cholesterol-poor lipid composition of ER membranes. 15 Although ER membranes have a surface area comparable to or greater than the plasma membrane, only 0.5–1% of the total cellular cholesterol is found in the ER, compared with the 30–40% of the total cellular cholesterol contained in the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our previous structure–property relationship research regarding AIE systems for cell imaging studies, we have observed a number of molecular designs that allow for specific organelle targeting and staining: small hydrophobic systems are drawn to lipid droplets; hydrophobic molecules with long alkyl chains target the phospholipid bilayer; positively charged compounds stain the mitochondria due to the organelle's membrane potential . However, there have been limited examples of molecules that are capable of staining the ER . The ER is a large membrane‐bound compartment spread throughout the cytoplasm of eukaryotic cells, which is composed of one completely continuous membrane bilayer and has a single continuous lumen.…”
Section: Introductionmentioning
confidence: 99%
“…The ER is a large membrane‐bound compartment spread throughout the cytoplasm of eukaryotic cells, which is composed of one completely continuous membrane bilayer and has a single continuous lumen. The ER plays a key role in cellular metabolism, protein synthesis, and the transport of intermediates and signaling molecules . Characterization of the ER structure in living cells is challenging due to a wide 3D interconnected network of flattened, membrane‐enclosed sacks or tube‐like cisterns and tubules with different thicknesses …”
Section: Introductionmentioning
confidence: 99%